Pseudoephedrine ingestion and cycling time-trial performance - Pritchard-Peschek, K. R.; Jenkins, P. G.; Osborne, M. A.; Slater, G. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
The aim of the current study was to investigate the effect of 180 mg of pseudoephedrine (PSE) on cycling time-trial (TT) performance. Six well-trained male cyclists and triathletes (age 33 ± 2 yr, mass 81 ± 8 kg, height 182.0 ± 6.7 cm, VO2max 56.8 ± 6.8 ml · kg-1 · min-1; M ± SD) underwent 2 performance trials in which they completed a 25-min variable-intensity (50-90% maximal aerobic power) warm-up, followed by a cycling TT in which they completed a fixed amount of work (7 kJ/kg body mass) in the shortest possible time. Sixty minutes before the start of exercise, they orally ingested 180 mg of PSE or a cornstarch placebo (PLA) in a randomized, crossover, double-blind manner. Venous blood was sampled immediately pre- and postexercise for the analysis of pH plus lactate, glucose, and norepinephrine (NE). PSE improved cycling TT performance by 5.1% (95% CI 0-10%) compared with PLA (28:58.9 ± 4:26.5 and 30:31.7 ± 4:36.7 min, respectively). There was a significant Treatment × Time interaction (p = .04) for NE, with NE increasing during the PSE trial only. Similarly, blood glucose also showed a trend (p = .06) for increased levels postexercise in the PSE trial. The ingestion of 180 mg of PSE 60 min before the onset of high-intensity exercise improved cycling TT performance in well-trained athletes. It is possible that changes in metabolism or an increase in central nervous system stimulation is responsible for the observed ergogenic effect of PSE.